Improving access and equity in reducing cardiovascular risk: the Queensland Health model. Issue 3 (16th February 2015) - Ski, Chantal F; Vale, Margarite J; Bennett, Gary R; Chalmers, Victoria L; McFarlane, Kim; Jelinek, V Michael; Scott, Ian A; Thompson, David R
Abstract: Objectives: To measure changes in cardiovascular risk factors among patients with coronary heart disease (CHD) and/or type 2 diabetes enrolled in a centralised statewide coaching program delivered by telephone and mail‐out in the public health sector in Queensland. Design: A population‐based audit of cardiovascular risk factor data collected prospectively as part of The COACH (Coaching Patients On Achieving Cardiovascular Health) Program (TCP) delivered through Queensland Health's Health Contact Centre. Setting and participants: 1962 patients with CHD and 707 patients with type 2 diabetes who completed TCP from 20 February 2009 to 20 June 2013, of whom 145 were Indigenous Australians. Main outcome measures: Changes in fasting lipids, fasting glucose, glycosylated haemoglobin levels, blood pressure, body weight, body mass index, smoking, alcohol consumption and physical activity, as measured at entry to and completion of the program. Results: Statistically significant improvements in cardiovascular risk factor status, from entry to completion of the program, were found across all biomedical and lifestyle factors in patients with CHD and/or type 2 diabetes. For both diseases, improvements in serum lipids, blood glucose, smoking habit and alcohol consumption combined with increases in physical activity were the most notable findings. Similar differences were found in mean change scores in cardiovascular risk factors between Indigenous and non‐Indigenous Queenslanders. Conclusion: A centralised statewide coaching program delivered by telephone and mail‐out overcomes obstacles of distance and limited access to health services and facilitates a guideline‐concordant decrease in cardiovascular risk.